Comparison of the factor structure of the patient health questionnaire for somatic symptoms (PHQ-15) in germany, the netherlands, and china: a transcultural structural equation modeling (SEM) study - Leonhart, Rainer; de Vroege, Lars; Zhang, Lan; Liu, Yang; Dong, Zaiquan; Schäfert, Rainer; Nolte, Sandra; Fischer, Felix; Fritzsche, Kurt; van der Feltz-Cornelis, Christina M. (Frontiers in psychiatry, 2018)
Persistent somatic symptoms are associated with psychological distress, impaired function, and medical help-seeking behavior. The Patient Health Questionnaire (PHQ)-15 is used as a screening instrument for somatization and as a monitoring instrument for somatic symptom severity. A bifactorial model has been described, with one general factor and four orthogonal specific symptom factors. The objective of the present study was to assess and to clarify the factor structure of the PHQ-15 within and between different countries in Western Europe and China. 5520 |s|factor structure